2017
DOI: 10.18805/ijare.v51i04.8423
|View full text |Cite
|
Sign up to set email alerts
|

Soil structure of pistachio cultivation areas in Turkey and comparison with border lines

Abstract: Pistachio orchards and the frontier zone which had been laid with mines for a long time were determined as research area. Soil samples from mined area, cultural practices applied (use of pesticides, soil tillage and artificial fertilizers) and naturally growing pistachio orchards were taken to compare physical, chemical, biological characteristics and heavy metal contents. Experimental soils generally consisted of clay, clayey-loamy, silted-loamy, sandy loamy clay and loamy, included alkalireaction and were li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the WA results indicated that the aforementioned Bacillus species preferred low metal concentrations. The sites of Area III were associated with high Zn and Mn levels [9] and were characterized by B. amyloliquefaciens, B. mycoides, and B. pumilus assemblages (Figure 3). The results from the multivariable approach indicated that the aforementioned Bacillus species had high tolerance to Zn and Mn.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the WA results indicated that the aforementioned Bacillus species preferred low metal concentrations. The sites of Area III were associated with high Zn and Mn levels [9] and were characterized by B. amyloliquefaciens, B. mycoides, and B. pumilus assemblages (Figure 3). The results from the multivariable approach indicated that the aforementioned Bacillus species had high tolerance to Zn and Mn.…”
Section: Resultsmentioning
confidence: 99%
“…Canonical correspondence analysis (CCA) was used to examine the relationship between Bacillus species and environmental variables including macro-and microelements (N, P, Ca, Fe, Mn, Mg, Zn, Cu, Pb, Cd, and Cr), physical and chemical properties [Electrical Conductivity (dSm-1), soil pH, lime % (CaCO 3 ) and organic matter] of soil samples obtained from a previous study [9]. Environmental variables were transformed (ln(x þ 1), except for pH to decrease skewness [31].…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation